Empowering Health: A Comprehensive Concept Analysis of Breast Self-Examination for Proactive Breast Health Management - Naz, Sumaira; Thanasilp, Sureeporn; Wisesrith, Wasinee (National Journal of Community Medicine, 2024)
The review paper discusses the concept of breast self-examination (BSE), a vital screening method for early detection and diagnosis of breast cancer. It uses the Walker and Avant analysis method to develop an operational definition, identify critical attributes, antecedents, consequences, and empirical referents of BSE. BSE is crucial for early detection and survival rates, especially in developing countries. It is a cheap and accessible technique for detecting abnormal cells in normal breast tissue, making it useful in underdeveloped countries with limited resources. Defining attributes of BSE include breast awareness, breast examination for lumps and changes, a screening measure for detecting breast cancer, recommended timing after the menstrual period, primary prevention of breast cancer, self-awareness aiding in early detection, and cost-effectiveness in resource-poor countries. The paper also discusses antecedents and consequences of BSE, including knowledge and perception about BSE, personal and family history of breast cancer, health literacy campaigns, education level, increasing age, obesity, and reproductive factors. Conclusions of BSE include the practice of BSE and early detection of breast cancer, motivation towards screening, self-awareness, physical activity, and self-efficacy. The paper provides empirical referents for measuring and assessing BSE, such as structured questionnaires, scales based on health belief models, knowledge tests, and health action process approaches.